Effects of the program “Active and healthy older adults” on glycosylated hemoglobin levels and anthropometric status in patients with DM2 older than 59 years users of the ESSalud Ayaviri Medical Center, 2018 - Patthy Milagros Condori Choquepata (2019)
Objective: to determine the effect of the program “active and healthy older adults” on the levels ofhbA1c and anthropometric status in patients with DM2 older than 59 years users of the ESSalud AyaviriMedical Center - 2018. Methodology: quasi-experimental design study, longitudinal since two studygroups were formed with measures before and after the program, a sample of 113 older adults leaving91 participants after the selection tests were applied, with 51 being the study group and 41 the controlgroup. The program consisted of combined exercises (aerobic and anaerobic) alternating 15 “each for45 ‘in 5 days for a period of 12 weeks, plus a healthy eating talk for the control group. Results: beforethe application of the program, the physical activity level of the population was calculated, this being60.4% of low activity followed by 39.6% of moderate activity. After the application of the program itwas observed that there was no significant difference between 1st and 2nd measurement of HbA1c in elderly patients with DM2 (p> .05), likewise there was a clinical difference in the percentage valuesof 0.2% -1%, Regarding the BMI, there was a statistically significant difference between the first andsecond measurements (p <.05), as for the ICC a significant difference was obtained in the decreaseof its values during the second control as with the MNA test ( p <.05). Conclusion: at the level ofsignificance there were no changes in the HbA1c values after the exercise program, but there wereclinical percentage changes. On the other hand, if there was effect of the program on the patients’atropometric changes, there was finally no effect through the ICC on HbA1c levels.